(untitled) (Contemporary Issues in Social Sciences and Management Practices, 2023)
This research investigates the influence of Sustainable Human Resource Management (HRM) on Women Entrepreneurship Success (WES) in the context of the fashion industry in Southern Punjab, Pakistan. With a focus on boutiques, apparel, embroidery, sewing, beauty parlors, and jewelry businesses, the study aims to demonstrate how Sustainable HRM supports female entrepreneurship, utilizing Entrepreneurial Readiness as a mediator and Open Innovation as a moderator. Data was collected from 300 female entrepreneurs in Multan, Bahawalpur, and DG Khan Division through questionnaires. Structural equation modeling, mediation, moderation, regression, reliability, T-test, and ANOVA analyses were conducted to unveil the latest insights. The findings highlight that Sustainable HRM fosters women entrepreneurship by elevating entrepreneurial readiness and applying entrepreneurship theories. The study is region-specific, limited to Southern Punjab, and reveals potential variations in findings across diverse contexts. Emphasizing Open Innovation, Sustainable HRM, Entrepreneurial Readiness, and WES, the research suggests future exploration of variables such as education, training, unemployment, poverty, and gender discrimination. Notably, this study pioneers the examination of the interplay between Sustainable HRM and women entrepreneurial success in the Pakistani fashion industry, introducing a novel perspective beyond the traditional focus on entrepreneurial readiness and entrepreneurship.